FACTORS INFLUENCING SPEAKING ANXIETY AT ONE PUBLIC UNIVERSITY IN JAMBI: LANGUAGE AND ACADEMIC ASPECTS - Mercy Sokoy (JAMBI-ENGLISH LANGUAGE TEACHING, 2023)
The general purpose of this study was to explore what are the factors influencing English learners’ felt anxious while speaking and the strategy used by the students’ to overcome they speaking anxiety. This study used qualitative method with case study approach; to collect the data the researcher used interview and documents. The result of this study indicated there were two factors influencing students speaking anxiety (language proficiency and academic proponent). Other than that the students also has their own strategy (language related management and self-management). The finding shows that language proficiency is the most significant factor made the English learner felt anxious when they want to speak. Language related management is best way for English learners to overcome their speaking anxiety.